Doctrinal Review on The Legality of Ulayat Rights Release Agreements in Papua Province - Kenny Cetera; Gagah Satria Utama (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
In Papua Province, land conflicts between MHA and entrepreneurs often occur and lead to social conflicts. One of the common practices used in the transfer of ulayat land is the Ulayat Rights Release Agreement. In this article, the author will discuss the legal aspects of the Ulayat Rights Release Agreement that need to be considered to protect the seller and the buyer. This study is a normative or doctrinal research that uses primary data in the form of observations and the author's experience as a legal analyst involved in the Papua Province licensing review process, as well as secondary data derived from statutory regulations and other literature. The results showed that Ulayat Rights Release Agreement requires three important conditions, namely: 1) Subjects that need to be legally identified and ratified (Ulayat Rights Holder); 2) Objects that need to be mapped (Ulayat Rights Limits); and 3) Relationship between Subjects and Objects about how Ulayat Rights are used, regulated, and managed by Ulayat Rights Holder (Ulayat Rights Control). These three points need to be legally ratified based on applicable regulations, which is through a Regional Head Decree or Regency Regulations. Keywords: MHA, Ulayat Rights, Papua